Cecropia manauara (Urticaceae), a new species from the Brazilian Amazon - Daniel Praia Portela de Aguiar; Layon Oreste Demarchi; Maria Teresa Fernandez Piedade; Rosane Garcia Collevatti; Paulo Roberto Da-Silva; Henrique Borges Zamengo de Souza; André Luiz Gaglioti (Acta Botânica Brasílica)
Abstract A new species of Cecropia (Urticaceae) is described for Amazonas state, Brazil. Collecting and processing of the vouchers followed the usual procedures for botanical specimens. Parallel to the herbarium procedures, phylogenetic analyses were performed and photographs of the species in the field were obtained. The species shares morphological similarities with Cecropia membranacea and C. concolor, which are discussed in this paper. It appears as a sister group of C. membranacea in the phylogenetic analysis in a strongly supported clade. An identification key for all known Cecropia species from the Central Amazon is provided. The conservation status of the new species is Vulnerable since it was only collected in Manaus municipality, occurring in the edges and vicinity of secondary “terra firme” forests and anthropized urban areas. The species is the tenth described for the Central Amazon.